The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

Interview Study on Strategy Options for Platform Operation in B2B Markets - Özcan, Leon; Fichtler, Timm; Kasten, Benjamin; Koldewey, Christian; Dumitrescu, Roman
Keywords: Digital Platform; Platform Strategy; Strategic Management; Platform Life Cycle; Interview Study; Business Model; Business-to-Business; Two-sided Market; Multi-sided Market

Performance Management Approach for Digital Platforms in B2B Markets - Özcan, Leon; Kirchberg, Lisa; Koldewey, Christian; Dumitrescu, Roman (The Role of Innovation: Past, Present, Future)
Digital platforms have already led to disruptions in multiple B2C markets and are becoming increasingly dominant in B2B markets. As a result, more and more companies are trying to participate in the platform economy. However, the successful development and operation of a digital platform is associated with significant challenges, which leads to 85% of all platforms failing. A core challenge is the dynamic nature of the platform economy, with varying strategic objectives at different stages in the platform lifecycle. Platform operators must continuously monitor platform progress and adjust their strategy. Utilizing action research in the real-world platform project AI Marketplace, we developed a lifecycle-oriented performance management approach for digital platforms in B2B markets. It enables platform operators to reflect on their position in the platform lifecycle, derive relevant strategic objectives, and monitor them with suitable key performance indicators. Hence, allowing them to secure the long-term success of their platform business.
Keywords: Digital Platform; Two-Sided Market; Multi-Sided Market; Platform Lifecycle; Platform Monitoring; Performance Management

Why do Digital Platforms succeed or fail? - A Literature Review on Success and Failure Factors - Özcan, Leon; Koldewey, Christian; Duparc, Estelle; van der Valk, Hendrik; Otto, Boris; Dumitrescu, Roman
In the course of digitalization, digital platforms are unleashing their full disruptive potential and are already dominating the first industries (e.g., hotel industry). As a result of this success, more and more companies want to build their own platforms and participate in the success. However, building and operating a digital platform involves multiple challenges and most of such ambitions fail. Since most digital platforms fail, strategic leadership of digital platforms must consider both success factors and reasons for platform failure. For this purpose, we conducted a systematic literature analysis and identified 24 success as well as failure factors in 9 dimensions. From a scientific perspective, the article provides a structured analysis of success and failure factors of digital platforms, which previously did not exist in literature. Practitioners can use the resulting knowledge base to successfully manage platform activities and avoid pitfalls.
Keywords: Digital Platform; Multi-sided Market; Two-sided Market; Success Factor; Failure Factor

Current developments in the European corporate bond market - Franke, Benedikt; Kosi, Urska; Stoczek, Pia
This paper introduces a novel database on the European corporate bond market to analyze the role of transparency regulation and recent developments in bond markets. We use data from the European Securities and Markets Authority (ESMA) to build a comprehensive database covering daily corporate bond listing information in Europe starting in 2018. We then analyze the different market segments of the European bond market along four key areas: (i) time and cross-sectional trends in bond listings; (ii) composition of firms on the market; (iii) firms’ financial reporting transparency; (iv) bond contract terms. Furthermore, we discuss the impact of recent economic events on these key areas.
Keywords: Transparency regulation; Corporate bond; European market

The Impact of Product Differentiation on Retail Bundling in a Vertical Market - Endres-Fröhlich, Angelika Elfriede; Hehenkamp, Burkhard; Heinzel, Joachim
We study the effects of product differentiation on the bundling incentives of a two-product retailer. Two monopolistic manufacturers each produce a differentiated good. One sells it to both retailers, while the other only supplies a single retailer. Retailers compete in prices. Retail bundling is profitable when the goods are close substitutes. Only then is competition so intense that the retailer uses bundling to relax competition both within and across product markets, despite an aggravation of the double marginalization problem. Our asymmetric market structure arises endogenously for the case of close substitutes. In this case, bundling reduces social welfare.
Keywords: Retail bundling; upstream market power; double marginalization; product differentiation

Wage Bargaining and Employment Revisited: Separability and Efficiency in Collective Bargaining - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya (Scandinavian Journal of Economics)
We analyse the two-dimensional Nash bargaining solution (NBS) by deploying the standard labour market negotiations model of McDonald and Solow (1981). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems, such that the two solutions together replicate the solution of the two-dimensional problem if the NBS is applied. The axiom of Independence of Irrelevant Alternatives is shown to be crucial for this type of decomposability. This result has significant implications for actual negotiations because it allows for the decomposition of a multi-dimensional bargaining problem into one-dimensional problems---and thus helps to facilitate real-world negotiations.
Keywords: Labour market negotiations; efficient bargains; Nash bargaining solution; sequential bargaining; restricted bargaining games

The Decomposability of the Nash Bargaining Solution in Labor Markets - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya
In this paper, we analyze the two-dimensional Nash bargaining solution (NBS) deploying a standard labor market negotiations model (see McDonald and Solow, 1981; Creedy and McDonald, 1991). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems such that the (Cartesian) product of the solutions of these problems replicates the solution of the two-dimensional problem, if the NBS is applied. However, this decomposition fails for any solution concept that does not satisfy the axiom of Independence of Irrelevant Alternatives (IIA axiom). Our decomposition result has significant implications for actual negotiations, as it allows for the decomposition of a multi-issue bargaining problem into a set of simpler problems, in particular a set of single-issue bargaining problems. In this way, the decomposition may help facilitate negotiations in labor markets and also in other environments.
Keywords: Labor market negotiations; Efficient bargains; Nash bargaining solution; Sequential bargaining; Restricted bargaining games

Product market effects of IFRS adoption - Downes, Jimmy F; Flagmeier, Vanessa; Godsell, David (Journal of Accounting and Public Policy)
Prior literature finds that International Financial Reporting Standards (IFRS) adopters enjoy lower financing costs subsequent to IFRS adoption. We predict and find that mandatory IFRS adopters exploit lower financing costs to increase market share vis-à-vis non-adopters. This effect is robust across several different model specifications in a sample capturing the universe of public and private firms in the EU, in a matched sample of public and private firms, and in a public firm sample comparing mandatory and voluntary IFRS adopters. We further find that IFRS is associated with an increase (decrease) in industry sales concentration (competition), consistent with large public firms increasing market share. In supplemental analyses, we find that mandatory adopters issue more equity and debt after IFRS adoption and that larger market share gains accrue to those mandatory IFRS adopters that issue more equity and debt after IFRS adoption. Overall, we provide evidence of unintended product market consequences of IFRS adoption.
Keywords: Financial reporting regulationProduct market competition

Beyond crowd judgments: Data-driven estimation of market value in association football - Müller, Oliver; Simons, Alexander; Weinmann, Markus (European Journal of Operational Research)
Keywords: Crowdsourcing; Football; Market value; OR in Sports; Soccer